Mapeamento genético de marcadores DArT (Diversity Arrays Technology) em cana-de-açúcar (Saccharum spp.) - Silva, Daniel Garcia (2012)
Sugarcane is an important crop, cultivated in more than 90 countries, occupying an area of approximately 20 million of hectares. Modern varieties (Saccharum spp.) are highly heterozygous interspecific hybrids, polyploids and often aneuploids, with chromosome numbers between 100 and 130. Such characteristics explain the common opinion that the genome of sugarcane is the most complex among cultivated species, posing a challenge to breeding programs. As a contribution to the understanding of this complex genomic architecture, this study aimed to build the first linkage maps using exclusively DArT markers in sugarcane. The maps were built using a progeny derived from the cross between varieties largely used in the Brazilian breeding program of RIDESA (RB97327 x RB72454). The initial mapping population comprised 186 individuals. Total genomic DNA was extracted from axial buds, following the protocol of Al-Janabi et al. (1999). Using the DArT P/L core facility to generate DArT data, a total of 7680 markers were analyzed, of which 850 were polymorphic. The analysis of segregation patterns in the progeny revealed that 47% of the individuals in the progeny were in fact derived from selfing of the female parent RB97327. These individuals were analyzed as a distinct generation. Linkage analyses were then performed on two populations (from selfing and crossing) separately. The software OneMap was used to construct the maps. The established linkage criteria for linkage analysis were LOD-score ≥ 3.5 and recombination fraction ≤ 0.4. In the first map, built using data from individuals originated from selfing, from 850 polymorphic markers, 392 markers (segregating in a 3:1 manner) were used to create 80 linkage groups related to the variety RB97327. For the population derived from the biparental crossing, four linkage maps were built: an integrated map composed of 98 linkage groups including 632 markers (1:1 and 3:1); an integrated framework map, using a more conservative ordering criteria for the linkage groups, which was composed of 94 linkage groups; and two other linkage maps, one for each parent (RB97327 and RB72454), built to estimate the genome size of the varieties involved in this study. The total length of the linkage map built using data from individuals derived from selfing of the variety RB97327 was 828 cM. The total length of the integrated linkage map was 2848 cM. The lengths of the maps built for each parent, using data from individuals derived from crossing, were 1465 cM (RB97327) and 1976 cM (RB72454). Using the methodology of Hulbert et al. (1988), the estimated genome sizes for these varieties were 2811 cM e 3471 cM, respectively. The maps obtained in these cases covered a low percentage of the estimated genome sizes (52% and 57%). In spite of the low polymorphism, DArT markers showed to be an efficient technique to perform genotyping of sugarcane. Hundreds of polymorphic markers were generated in only one assay, using two methods of genome complexity reduction. These markers represent a new tool for genetic studies in sugarcane, especially if the low cost (USD/marker) involved in data production is considered.